PENERJEMAHAN RAMAH DIFABEL - Parwanto, Wendi; 'Afifah, Farida Nur (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
In the Al-Qur’an dan Terjemahannya Edisi Penyempurnaan 2019 published by the Ministry of Religion, there are still several disabled verses that have not been translated with disabled-friendly translations. Even though at the launch of the QTK in the 2019 edition, it was explained that this edition accommodates responssive and disabled-friendly translations. Thus, this study needs to be conducted to explain how translations are ‘considered’ friendly for persons with disabilities by the Ministry of Religion. The type of this research is library research, using descriptive-analytic methods and using Peter Newmark’s translation theory. The conclusion of this study explains that: First, the translation of verses for physical and mental disabilities in the QTK 2019 edition tends to be inconsistent. Second, additional notes are still needed to make the reader understand, especially in emphasizing the information on verses that indicate disabilities, so as not to cause misunderstandings. Third, translations still tend to focus on the context of the verse, although the composition and structure of diction and sentences also need to be considered to create a disability-friendly translation. Fourth, there is no clear barometer in the QTK 2019 refinement edition, especially in translations that are ‘considered’ to be disabled-friendly.